2013
DOI: 10.3732/ajb.1200275
|View full text |Cite
|
Sign up to set email alerts
|

Polyploidization inHeuchera cylindrica(Saxifragaceae) did not result in a shift in climatic requirements

Abstract: Climatic niche differentiation does not explain the geographic distribution of tetraploid Heuchera cylindrica. We propose instead that tetraploid lineages were able to establish by taking advantage of glacial retreat and expanding into previously unoccupied sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 103 publications
(127 reference statements)
4
73
1
Order By: Relevance
“…niche modelling, genetic analyses, transplant experiments, etc.) have produced the same assortment of outcomes [118][119][120]. Here, rather than review previously proposed hypotheses of the distributions of polyploids relative to their parents in specific regions (e.g.…”
Section: (G) Novel Niches and Geographical Distributionsmentioning
confidence: 98%
See 1 more Smart Citation
“…niche modelling, genetic analyses, transplant experiments, etc.) have produced the same assortment of outcomes [118][119][120]. Here, rather than review previously proposed hypotheses of the distributions of polyploids relative to their parents in specific regions (e.g.…”
Section: (G) Novel Niches and Geographical Distributionsmentioning
confidence: 98%
“…Recent publications have assessed polyploid ecogeography using these techniques in a variety of systems [116,[118][119][120]131]; however, few conclusive patterns have emerged. Future studies must take into account phylogeny, type of polyploid and a wide variety of ecological variables at a scope so far unattained, yet achievable with current digitized resources.…”
Section: (G) Novel Niches and Geographical Distributionsmentioning
confidence: 99%
“…For example, diploid and hexaploid populations of Aster amellus are allopatric and occur in habitats that on average differ in degree of competition intensity, but in a common garden experiment there was no relationship between ploidy level and performance under competition [222]. Similarly, ecological niche modelling failed to identify climatic differences between populations of diploid and autotetraploid Heuchera cylindrica despite their spatial segregation across the US Pacific Northwest [206]. Among comparisons that are statistically significant, cytotype differences tend to more often be quantitative than qualitative, as recognized by Mü ntzing [1] many years ago.…”
Section: The Modern Era (A) An Influx Of Population Biologists (1980smentioning
confidence: 99%
“…Are such small differences in floral size likely to affect pollinator attraction? It has been proposed that changes in floral traits induced by polyploidy may promote a decrease in the frequency of interploidy pollination, thus allowing for the establishment of newly formed polyploids (Husband and Sabara, 2004;Kennedy et al, 2006;Godsoe et al, 2013). A few studies have provided evidence supporting the above prediction (Husband and Schemske, 2000;Kennedy et al, 2006).…”
Section: Discussionmentioning
confidence: 87%
“…Conversely, other studies, including reciprocal transplantation experiments, reported no niche differentiation between polyploids and their related diploids (Baack and Stanton, 2005;Godsoe et al, 2013;Glennon et al, 2014;L opez-Alvarez et al, 2015). Therefore, other mechanisms, including limited seed and pollen dispersal (Baack, 2005) and the capability of polyploids to colonize recently deglaciated areas (Stebbins, 1984;Brochmann et al, 2004;Godsoe et al, 2013;Theodoridis et al, 2013), have been invoked to explain the establishment of polyploids.…”
Section: Discussionmentioning
confidence: 99%